Health Care Reform in China - A Rural Rehabilitation Service Station - HL Qin; JG Ma; F Li; PS Mak; L Jieh; Ping-Chung Leung (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
A Rural Rehabilitation Service Station - an experimental model catered for elderlies and mildly disabled people is being established in a village near Xian, Shanxi Province. A non-government charity organization registered in Xian is responsible for the establishment. It has organized a team of Rural Medical Workers, Therapists, Traditional Chinese Medicine Doctors and Social Workers responsible for the development. The Service Station is receiving users regularly, and on special occasions workshops are organized. Professional support is regularly offered by one county hospital and a Charity Organization in Hong Kong. Towards the end of 2019, a proper review on the Service Station was be carried out by academics and professionals. It is expected that this unique establishment would provide valuable information for similar attempts to provide Rehabilitation Service in the rural areas of China.